EVALUASI KARAKTERISTIK FISIK BUBUK BAWANG PUTIH (Allium sativum L.) HASIL PENGERINGAN MENGGUNAKAN OVEN KONVEKSI - Purbasari, Dian; Yosika, Nur Ida Winni; Pambudi, Akbar Setyo; Ayun, Qurrota (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Universitas Jember, 2025)
Garlic (Allium sativum L.) is an important horticultural commodity widely used as a culinary spice and traditional medicine. Its high moisture content makes it highly perishable, thus requiring appropriate postharvest handling to extend its shelf life. One common method is drying using a convection oven, followed by powdering. This study aimed to evaluate the effect of drying temperature on the physical characteristics of garlic powder. The research was conducted from January to February 2020 at the Agricultural Product Engineering Laboratory, Faculty of Agricultural Technology, University of Jember. A Completely Randomized Design (CRD) was used with three temperature treatments (60°C, 70°C, and 80°C), each replicated twice. Observed parameters included moisture content, drying rate, drying yield, and color values (L*, a*, b*). Results showed that drying temperature significantly affected the physical properties of garlic powder. Higher temperatures reduced moisture content and L* values, while increasing a* values and water absorption capacity. These findings indicate that drying temperature is a critical factor influencing the final physical quality of garlic powder.